Human Resistance to Automation and the Fear of Job Displacement - Rüzgar, Nilüfer (IGI Global, 2025)
Using a new and complex technological system is stressful in itself, and this paradigm shift may not be immediately internalized by employees. This can cause high levels of technostress in employees, which can manifest itself as anxiety, timidity and frustrationThe concept of technostress is evaluated in multiple dimensions. In particular, the concept can trap employees in a negative psychological state that has a permanent effect on their physical, emotional and mental wellbeing. Employees feel that they always have to be alert and connected and therefore they can feel that they have no control on anything including their lives.In this sense, the purpose of this study is first to scrutinize the concept of technostress, which is caused by exposure to technology and especially to automation in organizations. The fear of job displacement is going to be handled in detail, since nowadays the most important cause of this fear is technology. © 2026 by IGI Global Scientific Publishing. All rights reserved.
Keywords: Complex technological systems; IS technologies; Job displacement; Multiple dimensions; Paradigm shifts; Psychological state; Technostress; Wellbeing; Personnel